2016
DOI: 10.1042/bst20150214
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of PtdIns(3,4,5)P3/Akt signalling by inositol polyphosphate 5-phosphatases

Abstract: The phosphoinositide 3-kinase (PI3K) generated lipid signals, PtdIns(3,4,5)P3 and PtdIns(3,4)P2, are both required for the maximal activation of the serine/threonine kinase proto-oncogene Akt. The inositol polyphosphate 5-phosphatases (5-phosphatases) hydrolyse the 5-position phosphate from the inositol head group of PtdIns(3,4,5)P3 to yield PtdIns(3,4)P2. Extensive work has revealed several 5-phosphatases inhibit PI3K-driven Akt signalling, by decreasing PtdIns(3,4,5)P3 despite increasing cellular levels of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 117 publications
1
47
0
Order By: Relevance
“…PI3K activation is initiated by the engagement of receptor tyrosine kinases (RTKs) to extracellular growth factors, which recruits PI3K to plasma membrane-anchored receptors and results in the conversion of PI3K phosphorylates phosphatidylinositol(4)bisphosphate (PI(4)P) and phosphatidylinositol (4,5) bisphosphate (PI(4,5)P2) to phosphatidylinositol (3,4)bisphosphate (PI(3,4)P2) and phosphatidylinositol (3,4,5)trisphosphate (PI(3,4,5)P3). PI (3,4)P2 and PI (3,4,5)P3 subsequently bind to and activate multiple downstream effectors [2]. Among them, Akt is an important effector protein kinase which is highly activated in nearly 80% of gastric cancers (GCs), and its activation may serve as a biomarker for the diagnosis of GC and as a molecular target for treatment [3].…”
Section: Introductionmentioning
confidence: 99%
“…PI3K activation is initiated by the engagement of receptor tyrosine kinases (RTKs) to extracellular growth factors, which recruits PI3K to plasma membrane-anchored receptors and results in the conversion of PI3K phosphorylates phosphatidylinositol(4)bisphosphate (PI(4)P) and phosphatidylinositol (4,5) bisphosphate (PI(4,5)P2) to phosphatidylinositol (3,4)bisphosphate (PI(3,4)P2) and phosphatidylinositol (3,4,5)trisphosphate (PI(3,4,5)P3). PI (3,4)P2 and PI (3,4,5)P3 subsequently bind to and activate multiple downstream effectors [2]. Among them, Akt is an important effector protein kinase which is highly activated in nearly 80% of gastric cancers (GCs), and its activation may serve as a biomarker for the diagnosis of GC and as a molecular target for treatment [3].…”
Section: Introductionmentioning
confidence: 99%
“…Src Homology 2‐containing Inositol Phosphatase‐1 (SHIP‐1) controls the intracellular levels of PI3K product PIP3 and functions as a negative regulator of cytokine and immune receptor signaling . Deletion of the SHIP‐1 gene in mice leads to an immunological phenotype with overproduction of pro‐inflammatory cytokines, activation of myeloid cells, and severe inflammation in the lung .…”
Section: Introductionmentioning
confidence: 99%
“…Src Homology 2-containing Inositol Phosphatase-1 (SHIP-1) controls the intracellular levels of PI3K product PIP3 and functions as a negative regulator of cytokine and immune receptor signaling. 1,2 Deletion of the SHIP-1 gene in mice leads to an immunological phenotype with overproduction of pro-inflammatory cytokines, activation of myeloid cells, and severe inflammation in the lung. 3,4 Previous studies by our laboratory and others showed that whole-body SHIP-1 KO mice developed a type 2 like severe lung inflammation and lung fibrosis 5,6 These studies demonstrated that SHIP-1 plays an important role in maintaining lung homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Since WT knobs are enriched with PI(3,4)P2 it may hypothetically serve as a product of PIP3 hydrolysis by INPP5E or phosphorylation substrate for PI5K, a process typical for endosomal membranes (Posor et al, 2013). INPP5E in the medulloblastoma PC is mostly involved in converting PIP3 into PI(3,4)P2 (Eramo and Mitchell, 2016). However, the canonical route of PIP3 synthesis is via recruiting of class I and II PI3K occurring mostly during tyrosine kinase receptor activation during proliferation (Hawkins and Stephens, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…One important consideration comparing PC and olfactory cilia in mature OSNs is that ciliogenesis of the PC is typically induced in cell culture by serum starvation or during embryogenesis by growth factors targeting Shh and/or tyrosine kinase receptor PI3K/PIP3/Akt pathways (Eramo and Mitchell, 2016). Probably, at the terminal developmental stage OSNs lack input from Hedgehog signaling negatively regulated by PIP2 in the PC through TULP-3 and Gpr161 (Mukhopadhyay et al, 2010;ChĂĄvez et al, 2015;Wrighton, 2015;Xu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%